Single nucleotide polymorphism and expression of genes for immune competent cell proliferation and differentiation in radiation-exposed individuals - E. A. Blinova; V. S. Nikiforov; M. A. Yanishevskaya; A. A. Akleyev (Вавиловский журнал генетики и селекции)
It is known that ionizing radiation influences the expression of the genes that play a key role in the mechanisms of maintaining the stability of cellular homeostasis. As a rule, changes in the transcriptome of an exposed cell occur within the first 24 hours following radiation exposure. And it predetermines early response in the case of genome damage. Later on modulations in gene transcription activity are also possible and could result in a carcinogenic effect. However, in order to find the role of exogenous factors (ionizing radiation), it is also necessary to take into account the contribution of endogenous factors that are able to modify gene transcription activity. This is especially important for long after the onset of radiation exposure. Single nucleotide polymorphisms located in regulatory regions of the genes may belong to this group of factors. The objective of the current study was to analyze the influence of ionizing radiation on the transcription activity of the STAT3, GATA3, NFkB1, PADI4 genes, which regulate proliferation and differentiation of immune competent human cells; and to assess the potential influence of single nucleotide polymorphisms located in regulatory regions of the genes on the amount of mRNA. The study involved people who had been chronically exposed due to releases of radioactive waste into the Techa River. It was observed that 60 years after the onset of radiation exposure changes in the transcription activity of the NFkB1 and PADI4 genes were registered in people with cumulative doses to RBM within the range 78–3510 mGy. In people who had been chronically exposed, the effect of allelic variations in rs1053023, rs4143094, rs28362491, rs874881 on the level of mRNAs of the STAT3, GATA3, PADI4, NFkB1 genes has not been established.